CFD Simulation of Pre-Chamber Spark-Ignition Large Bore CNG Engine: Model Development, Practical Applications, and Experimental Validation - Soo-Jin Jeong; Seokpan Seo; Seong-Joon Moon (Energies)
This study develops and validates a three-dimensional CFD model for a 12 L large-bore active-type pre-chamber spark-ignition (PCSI) engine fueled by natural gas. The model incorporates an advanced Extended Coherent Flamelet Model (ECFM-3Z) with a tuned stretch factor to capture complex turbulence–flame interactions, flame propagation, and pollutant formation under ultra-lean conditions. By systematically varying pre-chamber geometries—specifically the orifice diameter, cone angle, diverging tapered nozzle, and volume—the simulations assess their effects on combustion dynamics, heat release rates, turbulent jet penetration, and emissions (NOx and CO). Model predictions of in-cylinder and pre-chamber pressure profiles, combustion phasing, and emission trends are validated against experimental data. The results demonstrate that optimizing pre-chamber and orifice configurations enhances turbulent mixing, accelerates flame development, and reduces local high-temperature zones, thereby suppressing NOx and CO formation. Although some discrepancies in NOx predictions persist due to limitations in current turbulence–chemistry models, the findings offer valuable insights for the design of high-efficiency, low-emission PCSI engines.